Peritoneal Lymphomatosis Imaged by F-18 FDG PET/CT - Park, Eun Kyung (Springer-Verlag, 2010)
Peritoneal lymphomatosis is uncommon, but when encountered is associated with aggressive histological subtypes of high-grade lymphoma, such as small-cell, large-cell, mixed large and small cell, non-cleaved, lymphoblastic Burkitt-like, and diffuse large B cell lymphomas. The CT findings of peritoneal lymphomatosis are linear or nodular peritoneal thickening, retroperitoneal lymphadenopathy, omental and mesenteric involvement with streak-like infiltrations or a bulky mass, bowel wall thickening, hepatosplenomegaly, and ascites. The authors report the first FDG PET/CT images of diffuse large B-cell lymphoma of small bowel origin associated with peritoneal lymphomatosis in a 69-year-old man. The lesions demonstrated intense FDG uptake in PET/CT images.